KONTRIBUSI KOORDINASI MATA-KAKI TERHADAP KETERAMPILAN DRIBBLING SEPAK BOLA PADA EKSTRAKURIKULER SEKOLAH DAARUN NAHDHAH - sadam, muhammad sadam (Pusat Pengembangan Olahraga Universitas Pahlawan, 2024)
The background of this research is the Contribution of Ankle Coordination to Football Dribbling Skills at the Daarun Nahdhah School Extracurricular in carrying out dribbling skills which are still not quite right, as can be seen from the results of the time test of dribbling ability. The aim of this research was to determine the coordination of soccer dribbling skills in extracurricular activities at Daarun Nahdhah School. In this research method, the author uses correlational or correlational research. The data collection technique was purposive sampling with inclusion and exclusion criteria. Data analysis in this study uses this correlation test to find a relationship between and prove the hypothesis of the relationship between two variables if the data for the two variables are in the form of intervals or ratios, and the data sources of the two or more variables are the same. The results showed that there was a significant and opposite relationship between the ankle-toe and dribbling skills with a correlation coefficient of 0.315 with a significance level of product moment analysis of the Sig value. (2-tailed) is smaller than α=0.001 (0.000 < 0.001). The conclusion in this study shows that there is a significant and opposite contribution between the ankles and the feet to dribbling the ball at the Daarun Nahdhah School. Keywords: Ankles, Dribbling the Ball,